Results of Surgical and Conservative Treatment for Enterocutaneous Fistulas. Is there an Indication for Conservative Treatment? - Schildberg, C. W.; Raptis, Dimitrios; Langheinrich, M.; Hohenberger, Werner; Horbach, T. (Zentralblatt für Chirurgie, 2016)
The manifestation of enterocutaneous fistulas is varied. They can range from controlled secretion via the abdominal wall to septic disease. The disease is categorised into low-, moderate- and high-output fistulas. Often the only option is surgical treatment. Occasionally, there is spontaneous healing under conservative treatment. The aim of this study was to work out a possible subgroup of patients who benefit from conservative treatment. Material und Methods: Ninety-nine patients were treated for enterocutaneous fistulas from 1 January 1995 to 31 December 2005. Seventy patients underwent surgery, 29 patients were treated conservatively. All data was collected prospectively using an admission form and was analysed retrospectively. Conservative treatment consisted of fasting with parenteral nutrition, while fistulas in the surgical group were treated by suture repair or resection. Additive treatments such as vacuum dressings or TNF-? medication for patients with Crohn's disease were not performed.In our study we achieved a total cure rate of 69%, with an average hospital stay of 38 days. Surgical treatment led to significantly better results compared with conservative treatment (83 vs. 34%). Mortality in the surgical group was distinctly, but not significantly reduced at 7%, compared with 14% in the conservative group. The fistulas that healed after conservative treatment were low-output fistulas only.Enterocutaneous fistulas are diseases associated with long hospital stays and, therefore, expensive treatment. Low-output fistulas may heal spontaneously. The best results are achieved by surgical treatment. More recent treatments such as vacuum therapy and TNF-? medication for patients with Crohn's disease are promising approaches. In the future, many of these will have to be combined with surgical treatment.
EVALuna2:15208